2010
DOI: 10.1051/pmed/2010013
|View full text |Cite
|
Sign up to set email alerts
|

Formation au raisonnement clinique : perspectives d’utilisation des cartes conceptuelles

Abstract: Manuscrit reçu le 31 juillet 2009 ; commentaires éditoriaux formulés aux auteurs le 22 février 2010 ; accepté pour publication le 16 juillet 2010Mots clés : Raisonnement clinique ; cartes conceptuelles ; organisation des connaissances ; formation en sciences de la santé Résumé -Contexte : Le raisonnement clinique développé par les professionnels de santé est une manifestation de leur compétence à résoudre les problèmes posés par les patients. La littérature fait état d'un certain nombre de recommandations perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
5
0
3
Order By: Relevance
“…C'est aussi le cas des sciences de la santé, où la CC est utilisée principalement au niveau du cursus préclinique, surtout en médecine et en sciences infirmières [4,5] .…”
Section: Problématiqueunclassified
“…C'est aussi le cas des sciences de la santé, où la CC est utilisée principalement au niveau du cursus préclinique, surtout en médecine et en sciences infirmières [4,5] .…”
Section: Problématiqueunclassified
“…Their relevance and content validity for that purpose have been recognized for training and diagnostic assessment [31]. And while the authors do not believe that the psychometric qualities of concept mapping are sufficient for certification assessment in general education, the latter is not an issue in therapeutic patient education.…”
Section: Concept Maps Used At Different Stages Of Tpementioning
confidence: 99%
“…However, in their literature analysis on the use of concept mapping in medical education, Daley and Torre [35] showed that concept maps helped improve critical thinking and problemsolving, regardless of the learner's learning style. Recently, Demeester demonstrated the value of concept mapping in the acquisition of clinical reasoning skills [31].…”
Section: Little Exploration Of Cm's Effects On Patientsmentioning
confidence: 99%
“…In the field of health, concept maps (CM) are used to develop and evaluate the skills of professionals in training [1]. CM is mainly used in the preclinical curriculum, especially in medicine [2].…”
Section: Introductionmentioning
confidence: 99%